Assessment of pesticide residues in beef feed and meat in Bangladesh: A safety issues - MT Kamal; M Al-Mamun; MM Hossain; MA Razzaque; MA Hashem (Meat Research, 2022)
The use of pesticides in agricultural sectors is rising due to the growing demand for food in the world, but the presence of pesticide residues in agricultural commodities has become a major health concern for consumers and is associated with problems of food safety. Pesticides in meats and milk were derived from feeds. The present study was conducted to find the pesticide residue in cattle feed ingredients, commercial beef cattle feed and meat of beef cattle. Commercial beef cattle feed, Heart, kidney, liver, lung and muscle samples of beef cattle were collected from four district of Bangladesh were analyzed by GC-MS (Gas chromatography–mass spectrometry) for organochlorine and organophosphorus pesticide residue. There were no organoclhorine and organophosphorus pesticide residues in collected raw materials and commercial beef feed except Saudia and Fresh feed. In case of commercial beef feed. Aldrin was found in Saudia feed and Fresh feed at the level of 77 and 336 µg/kg, respectively. The results indicate that the concentration of aldrin in commercial beef cattle feed named Saudia and Fresh feed were above maximum residue limit (MRL) values (20 µg/kg) set by WHO/FAO. Contaminants existed at different levels in cattle feed of Bangladesh.